Stories of Supporting Constructivist Pedagogy Through Community - Kinnucan-Welsch, Kathryn; Jenlink, Patrick M. (Alberta Journal of Educational Research, 2001)
The conceptualization of professional development for educators is shifting from the prevalence of one-shot, quick-fix activities to a lifelong continuum of meaningful experiences, both within and outside of school. The purpose of this article is to examine how 102 educators over a span of three years explored constructivist pedagogy in the Cadre for Authentic Education, a professional development experience grounded in constructivist principles. The analysis of the qualitative data collected throughout the project suggested three stories that reflect the Cadre experiences: stories of frustration, stories of the importance of representing constructivism metaphorically, and stories of community. The stories represented in this article offer readers an opportunity to consider how teachers make sense of their underlying beliefs and assumptions as related to practice in the context of constructivist professional development experiences.